Economic Analysis of International Relations - Dikhtenko, O. O.; Cherepanova, V. O.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It is proved that the economic analysis of international relations is an analytical and synthetic study that combines the division of the object under study into its component parts and the integration of these parts at a new cognitive level. At the same time, economic analysis is a complex use of various methods of information transformation.
Економічний аналіз міжнародних відносин
Keywords: economic analysis; international relations; contradictions; factors